A bi-objective network design for value recovery of neodymium-iron-boron magnets: A case study of the United States. (20th February 2019) - Jin, Hongyue; Song, Byung Duk; Yih, Yuehwern; Sutherland, John W.
Abstract: Rare earth elements (REEs) such as neodymium (Nd) and dysprosium (Dy) are indispensable in modern society because they are vital for creating powerful neodymium-iron-boron (NdFeB) magnets used in many technological applications. These elements have been subject to a significant supply uncertainty. A promising strategy to alleviate supply risk is value recovery from end-of-life (EOL) products. This paper proposes a reverse supply network to optimize: 1) the locations and capacities of dismantling and recycling facilities, and 2) the transportation flows between collection centers, dismantling facilities, recycling facilities, and sales points. Two objectives are considered: maximizing profit and environmental benefits. A Pareto front is created that shows non-dominated optimal solutions. When the model was applied to the United States, California was found to be the most important state for EOL product collection, representing up to 22% of the total collection volume. Nevada, Tennessee, and Delaware were the key states for EOL product dismantling, and Nevada, Texas, and Delaware were the key states for NdFeB magnet recycling. A sensitivity analysis was performed to measure the impact of different NdFeB magnet price on the overall network design. While REE recovery is still at an early stage of the development, this research serves as a blueprint for constructing a profitable and environmentally friendly NdFeB magnet reverse supply chain.